Extending INSPIRE to accommodate urban drone logistics. Issue 26 (13th December 2022) - Bilgin, Gökhan; Anbaroğlu, Berk
Abstract: The use of drones in an urban environment, especially in the context of logistics, is expected to increase substantially in the coming years. This emerging technology poses a potential threat to other aircraft in the airspace, as well as to human beings and other assets on the ground. In order to mitigate these risks, it is vital to know where an automated drone is, where it is allowed to fly and when. Spatial Data Infrastructures (SDI) can be used as a useful tool to standardize automated drone flight data and facilitate the integration of drones into an airspace in a safe manner. This paper proposes an extension to the Infrastructure for Spatial Information in the European Community (INSPIRE). The proposed model is based on the relevant regulations of European Union (EU) and the Unites States of America (USA), and considers the state-of-the-art literature on drone logistics in an urban environment.